(untitled) (Asian Journal of Medical and Biological Research, 2016)
Withania somnifera (L) Dunal is commonly called as Ashwagandha/Asgand and it belongs to the family Solanaceae. It is a well known medicinal plant widely used in the treatment of many clinical conditions in Indian subcontinent. It is an important medicinal plant commonly known as Asgand which has been used either single or in combination with other drugs in Unani as well as Ayurvedic system of medicine for centuries. It has been described by Dioscorides (78 AD) in his book Kitab-ul-Hashaish. Asgand consists of the roots of Withania somnifera which has various therapeutic actions such as anti - inflammatory (Muhallil-e-Warm), sedative (Musakkin), aphrodisiac (Muqawwi-e-Bah), hepatoprotective, immune-modulator activity, anti-oxidant, anti-ageing, anti-tumour activity, adaptogenic activity and has anti-anticonvulsant activity. Keeping in view the medicinal properties of Withania somnifera Dunal (Asgand), an attempt has been made in this paper to explore various dimensions of the drug including phytochemical and pharmacological studies carried out on this herb. Asian J. Med. Biol. Res. June 2016, 2(2): 148-155